Physicochemical and Mineralogical Characterization of Ciuyah Mud Volcano: Rare Earth Elements and Salt Minerals for the Advanced Materials Industry, Indonesia - Nurfaradila, Fina; Agustine, Eleonora; Sartono; Nugroho, Amira Sasanti; Pranatikta, Krishna Agra (Spektra: Jurnal Fisika dan Aplikasinya, 2025)
The Ciuyah Mud Volcano in West Java is a notable geological feature resulting from mud extrusion driven by subsurface pressure, buoyancy, and thermal variations. Its unique characteristics provide valuable insights into Earth's subsurface processes. Materials ejected from mud volcanoes often contain valuable minerals that are crucial for scientific investigation and economic application. Of particular interest at this site is the presence of Rare Earth Elements (REEs), which are vital for modern technology. The aim of this study is to provide a comprehensive characterisation of the Ciuyah Mud Volcano. The objectives are to: (1) determine its physicochemical properties using electrical conductivity (EC), volumetric water content (VWC), and total dissolved solids (TDS) measurements; (2) identify the distribution of REEs using X-Ray Fluorescence (XRF) and Inductively Coupled Plasma-Optical Emission Spectrometry (ICP-OES); and (3) analyze the salt mineralogy using Scanning Electron Microscopy (SEM) and X-Ray Diffraction (XRD). The results revealed high conductivity in the mud, as evidenced by elevated EC and VWC values, as well as high TDS and salinity in the water samples. XRF and ICP-OES analyses confirmed the presence of twelve REEs: Ce, Dy, Eu, Gd, Ho, La, Nd, Pr, Sm, Tb, Sc, and Y. Furthermore, SEM and XRD identified Halite and Helvite as the primary salt minerals, characterized by large, hexagonal crystal structures. These findings highlight the potential of the Ciuyah Mud Volcano as a source of strategic REEs for Indonesia’s advanced materials and clean energy sectors, while also offering local socioeconomic applications, such as salt-based cosmetic products.